2003
DOI: 10.1016/s1074-7613(03)00019-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Contribution of TCR/pepMHC Affinity and CD8 to T Cell Activation

Abstract: The relative roles of CD8, TCR:pepMHC affinity, and TCR:pepMHC dissociation rate in T cell activation have remained controversial. To determine the relationships among these factors, we used T cells transfected with normal and in vitro engineered alphabeta TCRs, in the presence or absence of CD8. The TCRs exhibited a wide range of affinities (K(D) values of 80 microM to 5 nM). T cells with the highest affinity TCRs were efficiently stimulated by peptide, with or without CD8. In contrast, CD8 was required for T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
356
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(387 citation statements)
references
References 59 publications
30
356
1
Order By: Relevance
“…This point has perhaps not been given sufficient weight in many previous studies, possibly because most analyses on series of APLs have dealt with single amino acid variants of the antigenic peptide. However, its importance in determining the efficacy of a pMHC ligand has recently been shown in another TCR-pMHC system (13). Also, it has been noted that anomalies in the off-rate: biological response relationship are frequently seen in series of APLs that differ in MHC-interaction residues (8,10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point has perhaps not been given sufficient weight in many previous studies, possibly because most analyses on series of APLs have dealt with single amino acid variants of the antigenic peptide. However, its importance in determining the efficacy of a pMHC ligand has recently been shown in another TCR-pMHC system (13). Also, it has been noted that anomalies in the off-rate: biological response relationship are frequently seen in series of APLs that differ in MHC-interaction residues (8,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Some recent evidence consistent with serial triggering has been presented, where longer half-lives of complexes resulted in lower T cell activation than complexes with intermediate half-lives (7). However, a study where TCR affinity was greatly increased by mutagenesis showed increased T cell reactivity (13). This result argues strongly against serial triggering.…”
mentioning
confidence: 99%
“…Because the affinity of TCR/pMHC interaction is mainly controlled by its rate of dissociation (44), tetramer decay assays were performed to compare the stability of A2 and A2K b tetramer binding. Experiments were conducted using the NY-ESO-1 157-165 CTL lines H5 (Fig.…”
Section: Stability Of Tetramer Binding To Ctl Is Enhanced By the Presmentioning
confidence: 99%
“…In physiological T-cell activation, the activation efficiency correlates with the T-cell receptor (TCR) avidity to the cognate peptide-major histocompatibility complex (MHC) complex. [14][15][16][17][18] Optimal CD28 costimulation is provided by high-avidity engagement by dimeric B7.1 expressed on APCs, followed by dimer dissociation that facilitates downregulaton of CD28 and B7.1 internalization. 19 CD28 costimulation induces at least two independent activation pathways: one is integrated with TCR signalling in the context of synapse formation and is mediated through transcriptional enhancement and the second is mediated through increasing mRNA stability.…”
Section: Introductionmentioning
confidence: 99%